Calibration Method for Confocal X-Ray Microanalysis with Polychromatic Excitation - C. Sosa; V. Stoytschew; J. Leani; H. J. Sánchez; C. A. Pérez; R. D. Perez (Journal of Spectroscopy)
To apply the fundamental parameters method at the confocal setup the knowledge of the sensitivity of the spectrometer is required which depends on the characteristics of two X-ray lenses: one in the excitation channel and another in the detection channel. For the particular case of polychromatic excitation, the theory shows that the focalization properties of the excitation lens for all incident energies affect the X-ray fluorescence intensity. Therefore the traditional calibration method based on the measurement of standard samples becomes unstable since the number of required fitting parameters is too high. To reduce these parameters a previous characterization of the excitation lens by a simulation program was employed giving rise to a simplified confocal setup calibration. The developed calibration method was applied for a confocal spectrometer implemented in the Brazilian Synchrotron Radiation Source (LNLS) with white beam. The experimental parameters of the sensitivity were obtained from depth profile analysis of several pure thin films. The calibrated confocal setup was used to quantify reference standards in order to validate the calibration procedure. Our results for elemental concentrations show relative errors less than 15% for the quantitative analysis of a light matrix reference standard.